Modeling and simulation in biomedical engineering : applications in cardiorespiratory physiology - Meurs, Willem van, 1962- (New York : McGraw-Hill, 2011)
'This guide comprehensively covers everything from theory to practical application examples of modeling and simulation techniques of human physiology for medical engineers'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Cardiopulmonary system -- Computer simulation; Cardiopulmonary system -- Mathematical models; Biomedical engineering -- Methodology